Transcriptomic analysis of Malpighian tubules from the stingless bee Melipona scutellaris reveals thiamethoxam-induced damages - Miotelo, Lucas [UNESP]; Ferro, Milene [UNESP]; Maloni, Geovana [UNESP]; Otero, Igor Vinicius Ramos [UNESP]; Nocelli, Roberta Cornélio Ferreira; Bacci, Mauricio [UNESP]; Malaspina, Osmar [UNESP] (Elsevier, 2022)
The concern about pesticide exposure to neotropical bees has been increasing in the last few years, and knowledge gaps have been identified. Although stingless bees, (e.g.: Melipona scutellaris), are more diverse than honeybees and they stand out in the pollination of several valuable economical crops, toxicity assessments with stingless bees are still scarce. Nowadays new approaches in ecotoxicological studies, such as omic analysis, were pointed out as a strategy to reveal mechanisms of how bees deal with these stressors. To date, no molecular techniques have been applied for the evaluation of target and/or non-target organs in stingless bees, such as the Malpighian tubules (Mt). Therefore, in the present study, we evaluated the differentially expressed genes (DEGs) in the Mt of M. scutellaris after one and eight days of exposure to LC50/100 (0.000543 ng a.i./μL) of thiamethoxam (TMX). Through functional annotation analysis of four transcriptome libraries, the time course line approach revealed 237 DEGs (nine clusters) associated with carbon/energy metabolism and cellular processes (lysosomes, autophagy, and glycan degradation). The expression profiles of Mt were altered by TMX in processes, such as detoxification, excretion, tissue regeneration, oxidative stress, apoptosis, and DNA repair. Transcriptome analysis showed that cell metabolism in Mt was mainly affected after 8 days of exposure. Nine genes were selected from different clusters and validated by RT-qPCR. According to our findings, TMX promotes several types of damage in Mt cells at the molecular level. Therefore, interference of different cellular processes directly affects the health of M. scutellaris by compromising the function of Mt.
Keywords: De novo assembly; Differentially gene expressed; Excretion organ; Neonicotinoid; Sublethal effects